2011
DOI: 10.1080/13674676.2010.523890
|View full text |Cite
|
Sign up to set email alerts
|

Religion and spirituality in the context of bipolar disorder: a literature review

Abstract: Bipolar disorder (BD) affects approximately half a million Canadians. Religion and spirituality (R/S) may play an important role for individuals with BD by providing a means of coping with, and an explanatory model for, their disorder. We conducted a systematic review of empirical studies that have explored R/S in individuals with BD or samples that explicitly delineate individuals with BD. Only six studies met our inclusion criteria. Findings from these studies suggest that R/S strategies may be important for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 32 publications
1
19
1
Order By: Relevance
“…Despite the fact that S/R may play an important role in BD (Pesut et al, 2011), only 9% of patients with a BD in our sample report that S/R plays an essential role in terms of meaning in life. This may be due to the interaction between S/R and mood switches during the course of the illness.…”
Section: Discussioncontrasting
confidence: 62%
“…Despite the fact that S/R may play an important role in BD (Pesut et al, 2011), only 9% of patients with a BD in our sample report that S/R plays an essential role in terms of meaning in life. This may be due to the interaction between S/R and mood switches during the course of the illness.…”
Section: Discussioncontrasting
confidence: 62%
“…Similar results have been reported among 49 patients hospitalized with schizophrenia (Stolovy et al, 2009) and among 171 older adults reporting depressive symptoms (Westerhof et al, 2010). Pesut, Clark, Maxwell, and Michalak (2011) conducted a literature review concerning spirituality and BIPO in which they found only six articles. They found that individuals diagnosed with BIPO generally found that spirituality was beneficial to their coping with their symptoms, but noted that the benefit was no greater than that derived by the general population.…”
Section: Depressive Disordersupporting
confidence: 71%
“…Future studies would benefit from using longitudinal data and an experimental design to determine if there are causal connections between and among spirituality and meaning in life as they are related to mood disorders. In addition, since the questionnaire utilized in the current study provided only quantitative data, we were unable to determine whether connectedness to God in this sample was a protective factor against BIPO symptomatology or evidence of possible delusion as suggested by Pesut et al (2011). Future researchers may want to consider conducting face-to-face interviews to garner qualitative data on how individuals with BIPO view their relationship with a higher power.…”
Section: Limitations and Future Researchmentioning
confidence: 76%
See 2 more Smart Citations